ANALISIS EFEKTIVITAS PROGRAM SERTIFIKASI GURU DALAM PENING-KATAN KOMPETENSI PROFESIONAL: TINJAUAN DARI HASIL PENELITIAN - Asri Wulandari; Siti Maisaroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the effectiveness of the teacher certification program in enhancing teachers’ professional competence through a systematic review of previous research findings. Using a qualitative approach with the Systematic Literature Review (SLR) method, data were collected from relevant journal articles and research reports discussing the impact of certification on professional competence. The results reveal that the certification program has been effective in achieving its formal objectives, particularly in granting legal recognition and improving teachers’ welfare, which serve as motivational and psychological catalysts for professional growth. However, the program remains limited in transforming theoretical knowledge into innovative instructional practices in the classroom. The findings also highlight administrative burdens, variations in teachers’ initial qualifications, and insufficient managerial supervision as the main obstacles that hinder continuous professional development. Therefore, while certification is fundamental to teacher professionalization, it has not yet functioned optimally as a sustainable quality assurance mechanism. The study recommends repositioning certification as the starting point for continuous professional improvement rather than the ultimate goal of professional recognition.